Common variants in SOX-2 and congenital cataract genes contribute to age-related nuclear cataract - Ekaterina Yonova-Doing (Nature Portfolio, 2020)
Here, the authors report a multi-ethnic genome wide association meta-analysis of 12 studies from the International Cataract Genetics Consortium. They find six new loci associated with age-related nuclear cataract, in addition to replicating the association at CRYAA, and suggest a strong genetic link between age-related nuclear and congenital cataracts.